2000
DOI: 10.1128/jb.182.2.536-539.2000
|View full text |Cite
|
Sign up to set email alerts
|

The Feedback Response of Escherichia coli rRNA Synthesis Is Not Identical to the Mechanism of Growth Rate-Dependent Control

Abstract: Growth rate-independent rrn P1 promoter mutants were tested for their ability to respond to changes in rrn gene dosage. Most were found to be normal for the feedback response. In addition, cellular levels of the initiating nucleoside triphosphates remained unchanged when the rrn gene dosage was altered. These results suggest that the feedback response cannot be the mechanism for growth rate-dependent control of rRNA synthesis and that the relationship between these two processes may be more complicated than is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
(27 reference statements)
1
12
0
Order By: Relevance
“…Therefore, we favor the explanation that there may be additional mediators of feedback control of rRNA synthesis in E. coli. This conclusion is in agreement with that reached by Condon et al and Voulgaris et al, who reported that the ppGpp concentration did not decrease (9) and the ATP concentration did not increase (43) in strains with a reduced number of rRNA operons. Furthermore, these investigators noted that the activities of certain rrn P1 promoter variants that were relatively insensitive to the iNTP concentration were still subject to feedback control in strains with a reduced rrn gene dose.…”
Section: Vol 185 2003 Intp and Ppgpp In Feedback Control Of Rrna Sysupporting
confidence: 82%
See 1 more Smart Citation
“…Therefore, we favor the explanation that there may be additional mediators of feedback control of rRNA synthesis in E. coli. This conclusion is in agreement with that reached by Condon et al and Voulgaris et al, who reported that the ppGpp concentration did not decrease (9) and the ATP concentration did not increase (43) in strains with a reduced number of rRNA operons. Furthermore, these investigators noted that the activities of certain rrn P1 promoter variants that were relatively insensitive to the iNTP concentration were still subject to feedback control in strains with a reduced rrn gene dose.…”
Section: Vol 185 2003 Intp and Ppgpp In Feedback Control Of Rrna Sysupporting
confidence: 82%
“…Artificial manipulation of ribosome synthesis rates was used previously to demonstrate that a feedback mechanism(s) plays a role in the control of rRNA transcription. For example, when the rRNA gene dose was increased (21) or decreased (9,43), when rRNA was overexpressed from inducible promoters (18), when the fis gene was deleted or the rpoA gene was mutated (4,33,34), or when the rRNA antitermination system was disrupted (39), corresponding changes in rRNA core promoter activities always restored overall rRNA synthesis rates-and therefore ribosome synthesis rates-to the level appropriate for the nutrient condition. Thus, feedback mechanisms balance rRNA promoter activities with the need for protein synthesis.…”
mentioning
confidence: 99%
“…We also emphasize that the changes in rrnB P1 promoter activity associated with changes in growth rate or loss of the fis gene could be mediated only in part by variations in NTPs, and quantitative discrepancies in the correlations between the in vitro NTP-sensing behavior of the promoters and their in vivo regulatory responses could reflect the participation of other components in the system. Squires and coworkers have suggested that feedback elicited by an increased or decreased rRNA gene dose might be mediated by a mechanism distinct from that responsible for growth rate-dependent regulation and NTP sensing (60). They studied four rrnB P1 variants from our collection (T-33A, Ains-22, C-1T/C-15G, and C-1T) (17) and found an incomplete correlation between the cis-acting sequences required for growth rate-dependent regulation and those required for a response to gene dose changes.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship has been restated with the reference per amount of protein, e.g., "the synthesis of rRNA per unit amount of protein increases with the square of the growth rate and this phenomenon is called growth rate-dependent control of rRNA synthesis" (135). This statement derives from equation 2 above as follows.…”
Section: Relationship Between Rrna Synthesis and Growth Ratementioning
confidence: 99%
“…Although the original feedback models addressed the growth rate-dependent control of rRNA synthesis, it was later reported that "the feedback response of E. coli rRNA synthesis is not identical to the mechanism of growth rate-dependent control" (135). In that work feedback response and growth rate-dependent control were defined by the changes in LacZ enzyme expression from rrn P1 resulting from changes in either rrn gene dosage or growth medium, respectively (see the section Current Status of the Field, below).…”
Section: Ribosome Feedback Modelsmentioning
confidence: 99%